SOCIALIZATION OF THE VILLAGE SUSTAINABLE DEVELOPMENT GOALS (SDGS VILLAGE) DATA COLLECTION SYSTEM IN THE VILLAGE APPARATUS IN EAST KUTAI REGENCY - Aji Ratna Kusuma (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
This aim community service activities is to socialize to village officials, village representative bodies (BPD) and community leaders related to the Village SDGs program. The method that will be used in this Community Service is a Lecture that aims to provide knowledge about Millennium Development, Sustainable Development, and discussion and question and answer with participants to obtain an overview of their understanding of the material presented. The participants of the community service activities were the Village Head and the Secretariat Village apparatus of Bengalon District, East Kutai Regency, the Village Representative Body and its staff, and community leaders and several RT Chairmen. Based on the results of the socialization program of the village sustainable development goals data collection system, it can be concluded that this socialization understanding can provide an understanding to the community about village data collection activities in a complete manner regarding the SDGs and with this socialization can help village officials in compiling village data that meets the 18 criteria that are the objectives of the Village SDGs in an updated manner as well as material for the village ministry's assessment of the condition of the village concerned  to achieve the efficacy desired by the government. The usefulness of this service is as a basis for fulfilling the right of villagers to be healthy and free from poverty, as a basis for predicting what will be achieved until 2030 as soon as to anticipate obstacles that may be faced in the implementation of village development, and help the village government to identify village problems through complete data collection so that a detailed description of the village can be fulfilled in every program preparation  building.